Social acceptance and job satisfaction of ASHA workers in the Garo Hills Division of Meghalaya: a cross-sectional study - Mavelil, Sunny Joseph; Srivastava, S. C. (International Journal Of Community Medicine And Public Health, 2019)
Background: ASHAs were appointed by NRHM to provide preventive, promotive and curative healthcare services in the rural including tribal villages in Meghalaya. However, their social acceptance and job satisfaction remain less studied. Hence our study aimed at it. Methods: A cross-sectional study was conducted among 140 ASHAs from randomly sampled 142 villages across 15 PHCs in five districts. To collect data, we used a semi-structured back-translated and validated questionnaire consisting socio-demographic profile of ASHAs, level of perceived social acceptance and job satisfaction. Data were analysed using SPSS version 22.0. Results: Mean and median age of ASHAs were 33.29 and 32.00 years respectively. Over 63% belonged to Garo tribes, 67% studied high school, and 91% married. Village elders selected 76% of ASHAs, and 81% were as ASHAs for at least eight years. About 86% were trained in a minimum of three modules and all found their training effective. While 92% had the medical kit always filled, 100% had registers updated, and 94.3% facilitated VHND and FHD meetings. About 97% accompanied the pregnant women, 96.4% attended PHC meetings regularly and 83.6% organized VHSNC meeting. Though 93.5% reported a high acceptance of ASHAs’ services, social acceptance of ASHAs was rather to some extent for 36.4%. Almost 52% of ASHAs were dissatisfied with job and 61% were unhappy with their performance-based remuneration. Conclusions: Community must be aware of ASHAs’ role, and their job satisfaction has to be increased with a corresponding increase in incentives while developing strategies to ease the process of payments.